Water Soluble Aluminum Paste Using Polyvinyl Alcohol for Silicon Solar Cells - Abdullah Uzum; Taiki Ashikaga; Takuma Noguchi; Hiroyuki Kanda; Toshifumi Matsuoka; Toru Nakanishi; Hidehito Fukui; Tomitaro Harada; Seigo Ito (International Journal of Photoenergy)
Screen-printing aluminum is still dominantly used in the solar cell fabrication process. Ethyl cellulose is one of the main contents of screen-printing pastes that require dichloromethane for its cleaning process, a substance renowned for being extremely toxic and threatening to the human body. Developing environmental friendly aluminum pastes is essential in order to provide an alternative to the commercial pastes. In this work, new, nontoxic polyvinyl alcohol-based aluminum pastes are introduced. Polyvinyl alcohol was used as a soluble polymer that can be synthesized without saponification and that is also soluble in water. Three different pastes were developed using different recipes including many aluminum particle sizes varying from 3.0 to 45 μm, aluminum oxide with particle sizes between 35 and 50 μm, and acetic acid. Evaluation of the pastes was carried out by Scanning Electron Microscope (SEM) image analysis, sheet resistance measurements, and fabricating silicon solar cells using each paste. Solar cells with 15.6% efficiency were fabricated by nonvacuum processing on CZ-Si p-type wafers using developed aluminum pastes on the back side.